Factors associated with euphoria in a large subset of cases using propofol sedation during gastrointestinal endoscopy - Zhao, Kaixuan; Yang, Ning; Yue, Jingli; Han, Ying; Wang, Xiaoxiao; Kang, Ning; Zhang, Tianhao; Guo, Xiangyang; Xu, Mao (Frontiers in Psychiatry, 2023)
Background: TPropofol is a widely-used intravenous sedative or anesthetic that is known for its rapid action, easy control, and short half-life during general anesthesia and intensive care unit sedation. Emerging evidence indicates that propofol has notable euphoric effects, particularly in painless procedures, such as gastric or gastrointestinal endoscopy. Given its widespread use in patients undergoing such procedures, this study aims to investigate the clinical evidence and factors that may influence propofol-induced euphoria in these settings. Methods: The Addiction Research Center Inventory-Chinese Version (ARCI-CV) scale was administered to 360 patients undergoing gastric or gastrointestinal endoscopy using propofol as a sedative. Patient characteristics including past medical history, depression, anxiety, alcohol abuse, and sleep disturbance were recorded through history taking and assessment using various questionnaires prior to the examination. The euphoric and sedative statuses were assessed at 30 minutes and 1-week post-examination. Results: The experimental results of a survey of 360 patients who underwent gastric or gastrointestinal endoscopy using propofol showed that the mean Morphine–Benzedrine Group (MBG) score before the procedure and after 30 minutes of the procedure was 4.23 and 8.67, respectively. The mean Pentobarbital–Chlorpromazine–Alcohol Group (PCAG) score before the procedure and after 30 minutes of the procedure was 3.24 and 6.22, respectively. These results showed that both MBG and PCAG scores increased significantly after the procedure. Certain factors, such as dreaming, propofol dose, duration of anesthesia, and etomidate dose, were all correlated with MBG both at 30min and 1 week after the examination. In addition, etomidate had an effect of decreasing MBG scores and increasing PCAG scores both at 30min and 1 week after the examination. Conclusion: Taken together, propofol may elicit euphoria and potentially contribute to propofol addiction. There are several risk factors for the development of propofol addiction, including dreaming, propofol dose, duration of anesthesia, and etomidate dose. These findings suggest that propofol may have a euphoric effect and may have the potential for drug addiction and abuse.